Фундаментальні орієнтири в румунській фольклористиці - Константінеску, Н. (Народна творчість та етнологія, 2011)
A brief study of the history of the Romanian folkloristics reveals three leading scholars in that field before the mid-20th century: B. P. Hasdeu, O. Densusianu, and D. Caracostea. The centennial of the first lesson of folklore delivered at the Faculty of Letters of the University of Bucharest by the second of the three aforementioned scholars, O. Densusianu, was celebrated in 2009. Following the roads paved by his predecessors and mentors, M. Pop elucidated the field of folkloristics further and proposed new directions in the study of folk-literature in particular and folk culture at large.